Complete mitochondrial genome and phylogenetic analysis of Acanthogobius Hasta from the lower reaches of the Yangtze River. Issue 1 (2nd January 2019) - Zhang, Zhiyong; Zhang, Zhiwei; Zhu, Fei; Jia, Chaofeng; Meng, Qian; Sun, Ruijian; Chen, Shuyin; Wu, Guojun; Gao, Bo; Huang, Jiapeng
Abstract: In this study, the mitochondrial genome of Acanthogobius hasta was fully sequenced compared to other fish species mitochondrial genome. The genome is 16, 659 bp in length, including 2 ribosomal RNA genes, 13 protein-coding genes (PCGs), 22 transfer RNA genes, and a non-coding control region, the gene composition and order of which was similar to most reported from other vertebrates. Sequence analysis showed that the overall base composition is 27.8% for A, 28.0% for C, 17.4% for G, and 26.9% for T.